(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The present paper traces the development of feminism and post-feminism in the 20th century and shows how different theorists contributed to the development in their respective fields. It is in-depth analysis of the novel Maggie A Girl of the Streets by the American novelist Stephan Crane, from the post-feministic point of view. In the novel the young girl Maggie, in feministic terms, enjoys liberty of doing work and having equal liberty to those all living around her. She works in a sewing factory and has the liberty to drink beer or whisky but in the post-feministic terms she is still jailed. She is constrained by the social customs. She realises that she is forbidden to take decisions of her life when she falls in love with a guy named Pete. She is jilted in love and scorns of society force her to kill herself.